DRAFT TECHNICAL SPECIFICATIONS ON DESIGN AND INSTALLATION OF DIVIDED SCREENS FROM SOILCEMENT MADE DRIL-MIXING METHOD (Academic journal Industrial Machine Building Civil Engineering, 2017)
This a project of specifications on design and installation of dividing screens from soilcement elements, made by drill-mixing method. Keywords: separating screen, soil-cement element, drill-mixing method, new building, existing construction.